Budaya Baca pada Mahasiswa Pendidikan Bahasa dan Sastra Indonesia Universitas Negeri Makassar - Harlina Harlina; Ramly Ramly; Azis Azis (SOCIETIES: Journal of Social Sciences and Humanities, 2021)
Abstract. This study aims to: (1) describe the reading culture of PBSI Makassar State University students; (2) describe the factors that influence the reading culture of PBSI Makassar State University students; (3) describe efforts to improve reading culture in PBSI students at Makassar State University. This research is a qualitative research. The subjects in this study were students of class 2019 of the Indonesian Language and Literature Education study program, Faculty of Language and Literature, Makassar State University. Meanwhile, the object of this research is reading culture, the factors that influence the formation of reading culture, and the efforts made by students in improving reading culture. The data collection technique used in this research is in the form of a questionnaire. The data in this study were analyzed using data reduction, data presentation, and drawing conclusions and verification. The results of research related to reading culture in Indonesian Language and Literature Education students are at a very good level. There are eleven factors that influence the formation of reading culture in students. And, there are nine efforts made by students of Indonesian Language and Literature Education, Faculty of Language and Literature, Makassar State University in improving reading culture. Keywords: culture, reading, college student